2022
DOI: 10.1080/14756366.2022.2081844
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular modeling and biological evaluation of novel Benzoxazole-Benzamide conjugates via a 2-Thioacetamido linker as potential anti-proliferative agents, VEGFR-2 inhibitors and apoptotic inducers

Abstract: A novel series of 2-thioacetamide linked benzoxazole-benzamide conjugates 1 – 15 was designed as potential inhibitors of the vascular endothelial growth factor receptor-2 (VEGFR-2). The prepared compounds were evaluated for their potential antitumor activity and their corresponding selective cytotoxicity was estimated using normal human fibroblast (WI-38) cells. Compounds 1 , 9 – 12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The experimental procedures of in vitro biological evaluation assays including antiproliferative activities, [50,51,55] EGFR inhibition assay, [56] cell cycle analysis, [57] annexin V-FITC apoptosis assay, [57] Bax, Bcl2, Caspase-3-level expressions were conducted as reported previously. [58,59] All assay procedures were provided in detail in the Supporting Information data.…”
Section: Biological Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedures of in vitro biological evaluation assays including antiproliferative activities, [50,51,55] EGFR inhibition assay, [56] cell cycle analysis, [57] annexin V-FITC apoptosis assay, [57] Bax, Bcl2, Caspase-3-level expressions were conducted as reported previously. [58,59] All assay procedures were provided in detail in the Supporting Information data.…”
Section: Biological Evaluationsmentioning
confidence: 99%
“…[ 5–9 ] Protein kinases are involved in signal transduction pathways that regulate many physiological activities, including cell proliferation, differentiation, and death. [ 10–12 ] Growth factor receptor tyrosine kinases (TKs) are seen in a number of tumor forms, resulting in improper mitogenic signaling. Protein TKs are thus appealing targets in the quest for therapeutic drugs not just against cancer, but also against a wide range of other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 3, 5a-c, 6a-c, and 11a-e were synthesized as previously reported. 21,[36][37][38][39][40] 2.1.1. General procedure for the synthesis of target compounds 12-17.…”
Section: Chemistrymentioning
confidence: 99%
“…Condensation of the keton derivatives 5 and 6 with the appropriate acid hydrazides 10a-g (obtained according to the reported procedures) 16,23,24 at heating and reuxing temperature in absolute ethanol containing catalytic amount of glacial acetic acid afforded the respective hydrazono compounds 11a-e and 12a-g, respectively (Scheme 3).…”
Section: Chemistrymentioning
confidence: 99%
“…10 There drawbacks motivated the medicinal chemists to continue searching for new small molecules aiming to overcome the adverse effects and minimize resistance. [11][12][13][14] Observing the structure-activity relationship of the FDA approved VEGFR-2 inhibitors revealed that they almost shared four common features namely, (a) a heterocyclic head with minimum one nitrogen atom to occupy the hinge region of the active site, (b) a spacer to occupy gatekeeper region, (c) a hydrogen bonding moiety or a pharmacophore that makes essential H-bonds with the DFG amino acids, and (d) a hydrophobic tail that lls the receptor's allosteric site [15][16][17][18][19][20] (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%